Role of laser power and focus diameter in increasing retention of metal porcelain fixed dentures with short clinical crowns - Sutrisman, Andry; Putri Welda Utami Ritonga; Haslinda Z. Tamin (Indonesia Prosthodontic Association, 2024)
ABSTRACTBackground: In teeth with short clinical crowns that will be used as a support for metal porcelain fixed dentures, the problem that often occurs is that the dentures easily fall off after being installed. Surface treatment is one of the efforts to increase retention. Advances in laser technology provide advantages in increasing microstructural and wear resistance on the metal surface of the crown that will be used as abutment teeth.Objectives: In addressing the retention problem of short clinical crowns, modification of tooth preparation, casting, and proper cementation procedures need to be considered. Improving the mechanical properties by surface treatment of the dental crown to be cemented by modifying the strength and focus of the laser diameter can play a role in surface roughness and shear bond strength.Conclusion: The use of lasers to increase microstructural and wear resistance in teeth with short clinical crowns can minimize the failure of making metal porcelain fixed dentures. Keywords: fixed denture, short clinical crown, surface roughness, shear bond strength, laser